Using phenology to assess urban heat islands in tropical and temperate regions - Jochner, Susanne; Alves‐Eigenheer, Milene; Menzel, Annette; Morellato, Leonor Patrícia C. (International journal of climatology, 2013)
ABSTRACT The study of urban phenology is relevant to assess the effects of heat islands and the potential impacts of climate change on plants. Temperature is the main factor regulating plant development in moist/temperate regions. However, plants in tropical cities may respond to additional environmental cues, such as air humidity. We examined whether differences in air temperature and humidity along an urban–rural gradient influenced phenological onset dates of trees in a temperate mid‐latitude city (Munich, Germany) and a city in the neotropics (Campinas, Brazil). (Dis)similarities were identified incorporating equivalent study design based on identical methods for recording phenology and site‐specific meteorological data. We found that phenological onset dates of silver birch (Betula pendula) were able to describe local temperature variations in Munich. Correlation coefficients between mean temperature and onset dates of Betula were significant and varied between r = −0.48 and r = −0.72. However, onset dates for yellow trumpet tree (Tabebuia chrysotricha), false Brazilwood (Caesalpinia pluviosa) and rosewood (Tipuana tipu) in Campinas were rather variable, and the magnitude and significance of correlation coefficients with temperature varied greatly among species/phenophases. Nevertheless, we detected significant correlations, especially between Tipuana phenophases and temperature and between leaf unfolding of Tabebuia and humidity. Our findings revealed that the phenology of Tipuana was sufficiently sensitive to detect urban heat island effects in Campinas and might be a useful indicator of temperature variations and, in turn, of global warming. Because Tipuana is widely used for urban arborization in South America, we foresee many applications for monitoring heat islands in the neotropics. Furthermore, the fact that most phenophases of Tabebuia were not responsive to temperature stressed the importance of humidity variables. Additional species and phenophases should be explored to identify the further potential of phenology for monitoring heat islands in tropical cities.